STUDENTS' PERCEPTIONS OF USING THE EWA APPLICATION FOR ENGLISH LANGUAGE LEARNING - Warda Anggraeni; Anisa Alawiyyah; Handi Pabriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Digital learning has become increasingly central to English language teaching, and Mobile-Assisted Language Learning (MALL) applications such as EWA are now widely used by students as a supplementary learning tool. However, empirical understanding of how learners actually perceive and experience EWA remains limited. This study aimed to explore eleventh-grade students' perceptions of using the EWA application as a digital learning tool for English and to identify the difficulties they experienced while using it. A qualitative case study design was employed. Data were collected from 20 students through an open-ended questionnaire, followed by semi-structured interviews with five selected participants and supported by document analysis of learning artifacts. The data were analyzed using Braun and Clarke's (2006) six-phase thematic analysis. The findings show that students' perceptions of EWA cluster into three themes: Good Experience, Ease of Use, and Supportive Features, reflecting an application perceived as enjoyable, motivating, easy to navigate, and pedagogically useful, particularly for vocabulary, listening, and pronunciation. Nevertheless, students also reported difficulties grouped into four categories: Challenging content, Behavioral self-regulation issues, Technical issues, and Limitations arising from the freemium system. These difficulties did not diminish students' overall positive perception of EWA. The study concludes that EWA functions best as an engaging, flexible supplementary resource that complements, rather than replaces, formal classroom instruction. Further research involving larger and more diverse participant groups is recommended to strengthen the generalizability of these findings.